46 Service evaluation of the use of ketorolac at the macmillan palliative care unit (MPCU), Sheffield 2018–2019. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Ali, Maimoona; Davies, James
Abstract : Background: Ketorolac is used for pain control and also in pyrexia management at the end of life. It can be of significant benefit in severe pain related to cancer pain related to bone metastasis. This service evaluation was to see the use of Ketorolac, to see whether it's being used with clear indications and what documented side effects and adverse outcomes, if any, there are in the patients we've used it in. Methods: Patient details who were prescribed Ketorolac were retrieved from a report run on the electronic prescribing system. Electronic patient records and if needed paper clinical notes were reviewed with blood results viewed online for data collection. Data was then analysed on Excel. Results: 16 patients were prescribed Ketorolac whilst as an inpatient at MPCU (11/07/2018–30/07/2019). 11 out of 16 patients (69%) had their renal function checked prior to starting Ketorolac. 2 patients had is prescribed as a syringe driver, 7 patients had it prescribed regularly and 12 patients had it prescribed PRN. Following administration of Ketorolac 9 patients did not have their renal function checked. The most common reason documented for the bloods not been taken was the patient was for end of life care. Those patients when the renal function was checked there were no documented acute kidney injuries and their renal function was stable. No patient was discharged on Ketorolac. Conclusions: Patient centred care is a priority and the risk vs benefits of treatment options is challenging. This evaluation highlights that no patients had any documented acute kidney injuries who were prescribed Ketorolac. It will also enable the palliative medicine team to discuss with junior doctors, who regularly rotate, the importance of documenting decision making process which are individualised for our patients.